2017
DOI: 10.4209/aaqr.2016.03.0102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fingerprint and Source Identification of Atmospheric Fine Particles Sampled at Three Environments at the Tip of Southern Taiwan

Abstract: The spatiotemporal variation, chemical fingerprints, transportation routes, and source apportionment of atmospheric fine particles (PM 2.5 ) along the coastal region of southern Taiwan were investigated at three environments in the tip of southern Taiwan. Three representative sampling sites at Chien-Chin (urban site), Siao-Gang (industrial site) and Che-Cheng (background site) were selected for simultaneous PM 2.5 sampling from December 2014 to May 2015. Regular sampling of 24-h PM 2.5 was conducted for conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Previous research investigated the relationship between air pollutants and human health (Pope and Dochery, 2006;Cao et al, 2012;Heal et al, 2012;Pope and Dochery, 2013;Jin et al, 2017). Studies have shown that inhaling PM 2.5 can cause pneumonia and that it can dissolve in the bloodstream and cause heart and reproductive system diseases (Yang et al, 2017). PM 10 also has a significant impact on the mortality related to cardiovascular diseases and respiratory diseases (Abe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research investigated the relationship between air pollutants and human health (Pope and Dochery, 2006;Cao et al, 2012;Heal et al, 2012;Pope and Dochery, 2013;Jin et al, 2017). Studies have shown that inhaling PM 2.5 can cause pneumonia and that it can dissolve in the bloodstream and cause heart and reproductive system diseases (Yang et al, 2017). PM 10 also has a significant impact on the mortality related to cardiovascular diseases and respiratory diseases (Abe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2017) also showed that PM 2.5 /PM 10 ratios were mostly higher than 0.5 in southern Taiwan. By contrast, the PM 2.5 /PM 10 ratio was 0.26 for SdeBoker, an arid area, and it ranged from 0.6 to 0.80 for European and Western Mediterranean sites (Andreae et al, 2002).…”
Section: Pm Concentrations and Size Fraction Ratiosmentioning
confidence: 81%
“…Detailed information regarding the trajectory model and these data sets can be found on the NOAA Web site (http://www.arl.noaa.gov/re ady/hysplit4.html). This type of analysis has been widely applied in the environmental sciences; for instances, to investigate the long-range transport of pollutants and to establish the source-receptor relationships of air pollutants (Stohl, 1998;Xin et al, 2016;Ommi et al, 2017;Yang et al, 2017). Different air masses travel through different regions and therefore bring different chemical constituents with them, leading to different air quality characteristics in downwind areas (Abdalmogith and Harrison, 2005;Wang et al, 2006b;Kong et al, 2010).…”
Section: Backward Trajectory Analysismentioning
confidence: 99%
“…During the burning processes, levoglucosan was formed as an intermediate product which can be used as an indicator of biomass burning since cellulose was the main component of plant xylem. Moreover, K + has also been characterized as another valuable indicator of biomass burning since K + is highly abundant in the plant tissues 43 . The seasonal variation of levoglucosan concentration in PM 2.5 sampled at the Taiping Island is shown in Table S1 and Fig.…”
Section: Resultsmentioning
confidence: 99%